15 PAEDIATRIC TUBERCULOSIS MANAGED AT A CANADIAN CHILDRENS HOSPITAL: RELATIONSHIP TO BIRTHPLACE AND TRAVEL HISTORY. (19th August 2020) - Elhafid, Melanie; Morris, Shaun; Kourdi, Haifa; Waters, Valerie; Lam, Ray; Kitai, Ian
Abstract: Background: There are limited data about the relationship of child's birthplace, parents' birthplace, and travel history to paediatric tuberculosis (TB) acquisition and disease phenotype in Canada. Travel history is not routinely collected by public health authorities for cases of TB in Canada. Objectives: The objective of this study is to investigate the association of paediatric TB acquisition and disease phenotype at a metropolitan Canadian children's hospital with child's birthplace, parents' birth place, and travel history. Design/Methods: We reviewed prospectively collected TB clinic data (which include travel histories) and records of patients aged 0-17 years managed for active TB disease at a children's hospital ambulatory TB clinic between January 1, 2002 and December 31, 2018. Results: Two hundred and twenty six cases were identified, of which 116 (51%) were Canadian-born and 110 (49%) were foreign born children. Of the Canadian-born cases, only one case had parents who were both Canadian-born. In comparison to foreign-born patients, Canadian-born patients were more likely to have a history of travel to a TB-endemic country (63/104) [61%] versus (25/103) [24%], odds ratio [OR] 4.8; 95% confidence interval [CI] 2.6-8.7 p<0.001. Canadian-born patients were also more likely to have a known index case (80/116) [69%] versus foreign-born patients (23/110) [21%], OR 8.4; 95% CI 4.5-15.4, p<0.001. For Canadian-born patients, those without a known index case were more likely to have a history of travel to a TB-endemic country than those with a known index case (28/34) [82%] versus (35/70) [50%], [OR] 4.7 95% CI 1.7-12.7, p=0.02. Compared to Canadian-born patients, foreign-born patients had more extrapulmonary disease (48/109) [44%] versus (19/114) [17%], OR 3.9; 95% CI 2.1-7.3, p <0.001. Conclusion: Canadian-born children often acquired TB through contact with an infectious source in Canada. However, travel was likely important in a significant minority of cases, especially in Canadian-born children without a known index case. Post-immigration travel may also have been the source of TB in some foreign-born individuals. This would reduce the effectiveness of screening children for TB infection upon immigration. Strategies to prevent and detect travel-related TB are needed to reduce paediatric TB in areas with high immigration rates.